(untitled) (Journal of Civil Engineering Researchers, 2017)
With making of new materials and use those in construction projects, engineers and designers innovate various new structural forms which can be used in tall buildings execution. The structural form of building must be resist all combination of vertical and lateral loads. In general non-structural considerations have important effects in select of structural form and can be determinant. Furthermore, in slender and taller buildings structural parts have more importance and hence necessity to select of better structural form is more concern. In this paper dynamic response and performance of tall buildings with structural Tubular System (TS) and Bundled Tube System (BTS) against lateral loads have studied and compared. For this purpose, quadrangular plan by different heights have adapted. Spectral analysis has performed and the effect of parameters such as height of building, participation of higher modes, shear lag and the stiffness of perimeter beams have assessed. This research showed that performance of Bundled tube system structures from the view of above parameters variety is better than structural Tubular System and workable especially in shear lag reduction.